Synergistic toxicity against housefly Musca domestica of plant essential oils and their major constituents and safety against a non-target pollinator - Tanapoom Moungthipmalai; Cheepchanok Puwanard; Sirawut Sittichok; Mayura Soonwera (My University, 2023)
Abstract Plant essential oils (EOs) can fulfill the role of safe and effective fly repellent and adulticide. Individual and binary mixture formulations of Cymbopogon citratus (Stapf.) and Illicium verum (J. Presl.) EOs and their major constituents were assayed for their repellent and adulticidal activities against Musca domestica L. and non-target pollinator, Apis florea F. Their efficacy was compared to that of 1.0% (w/v) α-cypermethrin. A GC-MS analysis found that geranial and trans-anethole were the major constituents of C. citratus EO (45.23%) and I. verum (93.23%), respectively. All binary mixture formulations exhibited high and synergistic repellent and adulticidal effects: an increased repellent value between 18.7 to 57.6%, and a mortality rate value between 41.9 to 92.7%. The highest synergistic repellent effect was from 2.5% C. citratus EO + 2.5% I. verum EO, while the highest synergistic adulticidal effect was from 1.0% C. citratus EO + 1.0% trans-anethole. Both were more effective than 1.0% (w/v) α-cypermethrin. On the other hand, they were not toxic to the non-target pollinator. To conclude, C. citratus EO + I. verum EO and C. citratus EO + trans-anethole have a high potential as repellent and adulticidal agents against M. domestica which are safe for a pollinator, Apis florea.
Keywords: Cymbopogon citratus; Anethole; DEET; Insect Pest Control Strategies